ASSOCIATION OF BODY WEIGHT VARIABILITY AND BODY WEIGHT CHANGE WITH OUTCOMES IN THE SYSTOLIC BLOOD PRESSURE INTERVENTION TRIAL (SPRINT) - Richard Kazibwe, MD, MS; Matthew Singleton, MD, MBE, MHS, MSc; Arnaud D. Kaze, MD, MPH; Parag A. Chevli, MBBS, MS; Juliana H. Namutebi, MD; Ramla N. Kasozi, MD, MPH; Denis D. Asiimwe, MD; Joseph Yeboah, MD, MS (Elsevier, 2023)
Therapeutic Area: Obesity Background: Many people who try to lose weight fail to achieve sustained weight loss and instead experience cycles of weight loss and weight gain, a phenomenon referred to as "weight cycling". Such intra-individual body weight variability (BWV) has been linked to increased risk for cardiovascular (CV) disease and death, independent of other risk factors. The aim of this study was to examine the association between BWV and body weight change (BWC) with outcomes SPRINT. SPRINT enrolled individuals with high-risk hypertension but without diabetes mellitus (DM), to investigate the benefit of intensive (versus standard) blood pressure treatment on CV outcomes and all-cause mortality. Methods: In this analysis, we included a total of 8,714 SPRINT participants (age 67.8±9.4 years, 35.1% women) on whom data was available on serial weight during the study period. BWV was defined as the intra-individual average successive variability (ASV). BWC was defined as baseline weight minus exit weight. Using multivariate Cox regression models, we examined the hazard ratios (HR) associated with BWV and BWC (both as continuous variables), for all-cause mortality and the primary outcome [defined as the composite of myocardial infarction (MI), other acute coronary syndromes, stroke, acute decompensated heart failure (HF), or death from CV causes]. Results: Over a median follow-up of 3.9 years, the BWV and BWC [mean ± standard deviation (SD)] among participants were 3.12±3.04 and 1.01±6.97 kilogram respectively. Each 1 unit SD of BWV was significantly associated with a higher risk for all-cause mortality, primary outcome, MI and HF [HR (95% CI)]: 1.22(1.14-1.30; p<.0001), 1.13(1.07-1.19; p <.0001), 1.15(1.05-1.27; p=0.005), 1.10(1.00-1.20; p=0.047) and 1.16(1.07-1.26; p<.001) respectively (Figure). Similarly, each 1 unit SD of BWC was significantly associated with a higher risk for risk for all-cause mortality, primary outcome, MI and HF: 1.44(1.26-1.65; p<.0001), 1.11(1.02-1.21; p=0.017), 1.16(1.01-1.32; p=0.041) and 1.19(1.02-1.40; p=0.031) respectively (Figure). Conclusions: This study is consistent with significant independent risk for CV outcomes and all-cause death associated with weight fluctuations in patients with high-hypertension but without DM. In addition to recommending sustained weight loss, patients with high-risk hypertension should be counselled to minimize weight fluctuations.